2023
DOI: 10.1161/hypertensionaha.123.21112
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Diversities and Clonally Expanded Sequences of T-Cell Receptors in Patients With Essential Hypertension and Subclinical Carotid Atherosclerosis

Abstract: BACKGROUND: It has long been hypothesized that the abnormal immune responses contribute to the essential hypertension (EH) and its subclinical target organ damage (STOD). However, the mechanism is unclear. This study aimed at exploring the potential association with abnormal T-cell responses and EH, STOD, and early atherosclerosis in patients with EH. METHODS: This cross-sectional study included 146 patients with EH and 73 age-matched normotensive indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…As a further example, it has been shown that patients with EH or hypertension due to secondary causes like aldosterone-producing adenoma display a different type of TCR repertoire. 15 Ma et al 13 found a positive correlation between reduced T cell clone diversity and the number of antihypertensive drugs taken. This information could be related to the fact that patients with enhanced immune activation might have severe hypertension and, consequently, assume more drugs.…”
Section: See Related Article Pp 2318-2329mentioning
confidence: 99%
See 2 more Smart Citations
“…As a further example, it has been shown that patients with EH or hypertension due to secondary causes like aldosterone-producing adenoma display a different type of TCR repertoire. 15 Ma et al 13 found a positive correlation between reduced T cell clone diversity and the number of antihypertensive drugs taken. This information could be related to the fact that patients with enhanced immune activation might have severe hypertension and, consequently, assume more drugs.…”
Section: See Related Article Pp 2318-2329mentioning
confidence: 99%
“…12 In particular, high-throughput sequencing of the TCR provided valuable information on the computational landscape of T cell repertoire in relation to disease status. 12 In this issue, Ma et al 13 utilized high-throughput sequencing to analyze the peripheral TCR repertoire in patients with essential hypertension (EH) and evaluate the potential contribution of T cell response to disease progression. The authors evaluated the peripheral TCRβ (T cell receptor β-chain) clones in the peripheral blood mononuclear cells isolated from a considerable number of patients with EH (n=146) and normotensive subjects (n=73).…”
Section: See Related Article Pp 2318-2329mentioning
confidence: 99%
See 1 more Smart Citation